2017
DOI: 10.1002/job.2253
|View full text |Cite
|
Sign up to set email alerts
|

Societal individualism–collectivism and uncertainty avoidance as cultural moderators of relationships between job resources and strain

Abstract: SummaryThe job demands–resources model is a dominant theoretical framework that describes the influence of job demands and job resources on employee strain. Recent research has highlighted that the effects of job demands on strain vary across cultures, but similar work has not explored whether this is true for job resources. Given that societal characteristics can influence individuals' cognitive structures and, to a lesser extent, values in a culture, we address this gap in the literature and argue that indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 63 publications
1
46
0
Order By: Relevance
“…It could be that other ways of classifying countries may tell a different story. Some studies have, for instance, focused on different indicators of national culture, such as uncertainty avoidance, or on differences between individualist and collectivist cultures [92,127,128]. For instance, it is plausible that countries characterized by high uncertainty avoidance built their social safety nets in order to avoid employment uncertainty or to reduce the negative consequences of job insecurity [128,129].…”
Section: Discussionmentioning
confidence: 99%
“…It could be that other ways of classifying countries may tell a different story. Some studies have, for instance, focused on different indicators of national culture, such as uncertainty avoidance, or on differences between individualist and collectivist cultures [92,127,128]. For instance, it is plausible that countries characterized by high uncertainty avoidance built their social safety nets in order to avoid employment uncertainty or to reduce the negative consequences of job insecurity [128,129].…”
Section: Discussionmentioning
confidence: 99%
“…At a psychological level, a collectivist orientation is defined as the degree to which individuals hold a general orientation toward group goals, group norms, the well-being of the group and its members, and a tendency toward cooperation in the workgroup [23,24,25]. Scholars have demonstrated that one’s cultural orientation may affect the use or effectiveness of personal resources in the work context; employees with collectivist values are more willing to suppress personal goals for the good of the whole and for contributions made to the effective functioning of the organization [26]. Accordingly, we believe that a collectivist orientation may influence relationships between personal resources and work outcomes.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Although individuals' acceptance of cultural values varies within a society (Chatman & Barsade, 1995;Moorman & Blakely, 1995;van Dyne, Vandewalle, Kostova, Latham, & Cummings, 2000), collectivism is also a characteristic that differentiates one national culture from another (e.g., Fisher, 2014;Jang, Shen, Allen, & Zhang, 2018). The cultural values that the members of a society ascribe to on average influence the cognitive structures and schemas of those socialized within the society (Peterson & Barreto, 2014).…”
Section: Collectivism and Group Average Work Hoursmentioning
confidence: 99%